2018
DOI: 10.1159/000494445
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Pyruvate Attenuates CaCl<sub>2</sub>-Induced Tubular Epithelial Cell Injury by Inhibiting Autophagy and Inflammatory Responses

Abstract: Background/Aims: Nephrolithiasis is one of the most prevalent diseases of the urinary system. Approximately 80% of human kidney stones are composed of calcium oxalate (CaOx), and hypercalciuria is one of the most common metabolic disorders. Emerging evidence indicates that autophagy and inflammatory responses are related to the formation of CaOx nephrolithiasis. However, the roles of autophagy and inflammation in patients with hypercalciuria remain unclear. Ethyl pyruvate (EP) displays protective effects in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…In this study, we found that cell‐crystal reaction led to increased production of ROS and MDA and a decreased level of SOD, which contributed to the activation of oxidative stress. Consistent with our previous results, CaOx crystals significantly increased the secretion of LDH, the adherent and endocytosis of CaOx crystals in HK‐2 cells, and increased the levels of CRE and BUN in rat serum and the deposition of crystals in rat kidney . Yu et al reported that CaOx crystals increased the production of ROS and induced the damage to HK‐2 cells via mediating the AKT/P38/MAPK pathway.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we found that cell‐crystal reaction led to increased production of ROS and MDA and a decreased level of SOD, which contributed to the activation of oxidative stress. Consistent with our previous results, CaOx crystals significantly increased the secretion of LDH, the adherent and endocytosis of CaOx crystals in HK‐2 cells, and increased the levels of CRE and BUN in rat serum and the deposition of crystals in rat kidney . Yu et al reported that CaOx crystals increased the production of ROS and induced the damage to HK‐2 cells via mediating the AKT/P38/MAPK pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our previous results, CaOx crystals significantly increased the secretion of LDH, the adherent and endocytosis of CaOx crystals in HK-2 cells, and increased the levels of CRE and BUN in rat serum and the deposition of crystals in rat kidney. 20,22 Yu et al 23 reported that CaOx crystals increased the production of ROS and induced the damage to HK-2 cells via mediating the AKT/P38/MAPK pathway. The above data indicated that oxidative stress played a critical role in cell damage and intrarenal crystal formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from pyruvate, an important metabolite in the tricarboxylic acid cycle. EP repairs tissue or cell damage and enhances immunity by anti-oxidation and reducing the secretion and expression of inflammatory factors induced by LPS such as IL-1β, IL-6 and IL-8 [11][12][13]. EP also has a therapeutic effect of repairing intestinal barrier on enteritis induced by external stimuli [14].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (48) reported that in patients with calcium-containing kidney stones, an increased expression of HMGB1 and MCP-1 was found in their urine. The results of in vitro studies show that high calcium ions stimulate RTECs to activate the HMGB1-RAGE/TLR4-NF-kB signaling pathway and stimulate the secretion of inflammatory factors TNF-a, IL-1b, and IL-6 (49). Moreover, previous studies have also indicated that there is a close relationship between the secretion of HMGB1 and the activation of NLRP3 inflammasomes (50,51).…”
Section: Ros-induced Activation Of Nlrp3 In Macrophage-crystal Reactionmentioning
confidence: 89%